2016
DOI: 10.4238/gmr15048923
|View full text |Cite
|
Sign up to set email alerts
|

miR-1 association with cell proliferation inhibition and apoptosis in vestibular schwannoma by targeting VEGFA

Abstract: A growing body of research has demonstrated the tumor suppressive function of microRNA (miR)-1 in many cancers. Our study aimed to investigate its role in vestibular schwannoma (VS). We examined miR-1 expression in 95 VS specimens and 79 normal vestibular nerves using quantitative real-time polymerase chain reaction. Moreover, miR-1 mimics, miR-1 inhibitors, and negative control oligonucleotides were transfected into HEI-193 human VS cells to investigate the functional significance of miR-1 expression in this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 26 publications
1
6
0
Order By: Relevance
“…A previous study on zebrafish reported an antiangiogenic role for miR-1 and miR-206 (62). In line with this report, a few studies indicated that miR-1 targets VEGF in malignant cells (43,44). Our findings in VEGF transgenic mice and in the in vitro VEGF supplementation experiments strongly suggest that the antiangiogenic effects of miR-1 can occur independent of its anti-VEGF properties.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…A previous study on zebrafish reported an antiangiogenic role for miR-1 and miR-206 (62). In line with this report, a few studies indicated that miR-1 targets VEGF in malignant cells (43,44). Our findings in VEGF transgenic mice and in the in vitro VEGF supplementation experiments strongly suggest that the antiangiogenic effects of miR-1 can occur independent of its anti-VEGF properties.…”
Section: Discussionsupporting
confidence: 90%
“…Previous studies have shown that miR-1 regulates multiple aspects of the tumor cell behavior, such as proliferation (38,39), motility (27,40), apoptosis (41,42), angiogenesis (43,44), and glucose metabolism (45). Two recent studies suggested that miR-1 modulates the paracrine function of cancer-associated fibroblasts (46,47), and one recent report showed that ectopic miR-1 modulates the extracellular vesicles released from glioblastoma tumor cells (48).…”
Section: Discussionmentioning
confidence: 99%
“…miRNA is a class of non‐coding single‐stranded RNA molecules . miRNA binds to untranslated region (UTR) of target gene and regulates the expression of target gene at the posttranscriptional levels . It is now found that most protein‐coding genes in mammals are regulated by the expression of miRNAs.…”
Section: Discussionmentioning
confidence: 99%
“…The hypothesis that miR-1 may play a suppressive role in this tumor was further confirmed by the transfection of the HEI-193 cell line. Specifically, the overexpression of miR-1 led to a significant reduction in cell proliferation, enhancing the apoptotic process, while the knockout of miR-1 exerted the opposite effect (120). At the same time, in vitro experiments revealed that transfection with miR-1 mimic was negatively related to VEgFA levels.…”
Section: Altered Mirna Expression In Vestibular Schwannomamentioning
confidence: 93%
“…These findings suggest that miR-7 could potentially act as a tumor suppressor in vestibular schwannoma formation and growth by inhibiting the EgFR, pak1 and Ack1 signaling pathways (118). Of note, Li et al (120) focused on miR-1, a small non-coding RNA downregulated in various types of cancer (oral cancer, colorectal cancer, lung cancer, etc.) (121)(122)(123).…”
Section: Altered Mirna Expression In Vestibular Schwannomamentioning
confidence: 99%